Răspuns: [tex]\color{orangered}\Large\boxed{\bf x=\dfrac{6}{5} }[/tex]
Explicație pas cu pas:
[tex]\large\bf (x+5)\cdot (x+2)-3\cdot(4x-3)=(x-5 )^{2}[/tex]
[tex]\large\bf x^{2} +2x+5x+10 -3\cdot(4x-3)=(x-5 )^{2}[/tex]
[tex]\large\bf x^{2} +7x+10 -12x +9=(x-5 )^{2}[/tex]
[tex]\large\bf x^{2} +7x+10 -12x +9=x^{2} -10x+25[/tex]
[tex]\large\bf x^{2} -5x+19 =x^{2} -10x+25[/tex]
[tex]\large\bf x^{2} -5x+19 -x^{2} +10x=25[/tex]
[tex]\large\bf 5x+19=25[/tex]
[tex]\large\bf 5x=25 -19[/tex]
[tex]\large\bf 5x=6[/tex]
[tex]\color{red}\Large\boxed{\bf x=\dfrac{6}{5} ~~sau~ ~x=1\dfrac{1}{5}}[/tex]
#copaceibrainly